For this case we have a system of two equations with two unknowns:
![2x + 3y = 3\\7x-3y = 24](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5w2csaudpnhpk0tcm75kv5tskmn8yn391c.png)
We follow the steps below:
We add the equations:
![9x = 27](https://img.qammunity.org/2020/formulas/mathematics/middle-school/s3buxkl6zpnhuz8qsekscjq17663gfwnoe.png)
We divide between 9 on both sides of the equation:
![x = \frac {27} {9}\\x = 3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bfjhpj5cvqbnsckkm06mgclj5tvcqwth8n.png)
We substitute the value of "x" in the first equation and find the value of y:
![2 (3) + 3y = 3\\6 + 3y = 3\\3y = 3-6\\3y = -3\\y = \frac {-3} {3}\\y = -1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kz4ewuhk4by5ndizlx7ynmu5ds7lxbxd9i.png)
Thus, the solution of the system is: (3, -1)
Answer:
(3, -1)